Postawa ciała chłopców wiejskich z niedoborem i nadmiarem tkanki tłuszczowej w organizmie = Body posture of rural boys with deficiency or excess of body fat - Górniak, Krystyna; Lichota, Małgorzata; Popławska, Helena; Dmitruk, Agnieszka (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The aim of this study was to analyze the body posture and arches of the feet of rural boys with deficiency or excess of body fat, and to compare these parameters with those of participants with normal adiposity. The study was conducted in 2008 among rural children and adolescents from Biała Podlaska Province. Adiposity and body posture of 589 boys aged between 7 and 18 years were analyzed. Three groups of boys, with deficiency or excess of adipose tissue and normal adiposity, were identified on the basis of percentile charts of percentage body fat.
Keywords: body posture; adiposity; boys; chłopcy; otyłość; postawa ciała